Comparative de novo transcriptome analysis of flower and root of Oliveria decumbens Vent. to identify putative genes in terpenes biosynthesis pathway - Khodavirdipour, Amir; Safaralizadeh, Reza; Haghi, Mehdi; Hosseinpourfeizi, Mohammad Ali (Frontiers in Genetics, 2022)
The Oliveria decumbens Vent. is a wild, rare, annual medicinal plant and endemic plant of Iran that has metabolites (mostly terpenes) which make it a precious plant in Persian Traditional Medicine and also a potential chemotherapeutic agent. The lack of genetic resources has slowed the discovery of genes involved in the terpenes biosynthesis pathway. It is a wild relative of Daucus carota. In this research, the transcriptomic differences between 2 samples, flower and root of Oliveria decumbens, and also analyze the expression value of the genes involved in terpenoid biosynthesis by RNA-seq and its essential oil’s phytochemicals analyzed by GC/MS. In total, 136,031,188 reads from 2 samples of flower and root have been produced. The result shows that the MEP pathway is mostly active in the flower and the MVA in the root. Three genes of GPP, FPPS, and GGPP that are the precursors in the synthesis of mono, di, and triterpenes are upregulated in root and 23 key genes were identified that are involved in the biosynthesis of terpenes. Three genes had the highest upregulation in the root including and On the other hand, another three genes had the expression only in the flower. Meanwhile, 191 and 185 upregulated genes in the flower and root of the plant respectively, were selected for the gene ontology analysis and reconstruction of co-expression networks. The current research is the first of its kind on Oliveria decumbens transcriptome and discussed 67 genes that have been deposited into the NCBI database. Collectively, the information obtained in this study unveils the new insights into characterizing the genetic blueprint of Oliveria decumbens Vent. paved the way for medical/plant biotechnology and the pharmaceutical industry in the future.